Effects of MyBFF@school, a multifaceted obesity intervention program, on anthropometry and body composition of overweight and obese primary schoolchildren - Ruziana Mona Wan Mohd Zin; Abdul Halim Mokhtar; Abqariyah Yahya; Fuziah Md. Zain; Rusidah Selamat; Zahari Ishak; Muhammad Yazid Jalaludin (BMC Public Health)
Abstract Background Recently, there has been an increase in the prevalence of childhood obesity in Malaysia, raising concerns about increased cardiometabolic morbidity. MyBFF@school is a multifaceted program comprising physical activity, nutritional education, and psychological empowerment introduced to combat childhood obesity in Malaysia. The efficacy of a six-month intervention on the body composition of overweight and obese primary schoolchildren was evaluated. Methods This is a school-based, cluster randomized controlled trial involving selected primary schools in Kuala Lumpur, Selangor, and Negeri Sembilan. A total of 1,397 primary-school students aged 9–11 with a body mass index (BMI) $$z$$ z -score (corrected for age) greater than + 1 standard deviation based on the World Health Organization 2007 Growth Reference were assigned to intervention ( $$n=647$$ n = 647 ) and control ( $$n=750$$ n = 750 ) groups. BMI z-score, waist circumference (WC), percentage body fat (PBF), and skeletal muscle mass (SMM) were assessed at baseline and after three and six months of the study. Analyses of all outcomes except for the baseline characteristics were conducted according to the intention-to-treat principle. Results After three months, there was no significant difference in the BMI z-score or PBF between the control and intervention groups, but SMM and WC were significantly higher in the intervention group versus the control group with mean difference of 0.15 kg; 95% confidence interval [CI]: 0.07–0.22, p < 0.001 and mean difference of 1.53 cm; 95% confidence interval [CI]: 1.21- 1.85, p < 0.001 for SMM and WC respectively. After six months, the intervention group demonstrated a significantly greater reduction in PBF compared to the controls (% mean difference: 0.43%, 95% CI: − 0.73 to − 0.12, p < 0.001) as well as a greater increase in SMM (mean difference: 0.28 kg, 95% CI: 0.18–0.37, p < 0.001). There was no difference in the BMI z-score or WC between the intervention and control groups at six months. Conclusions The multicomponent MyBFF@school intervention significantly improved body composition among obese primary schoolchildren in terms of percentage body fat and skeletal muscle mass compared to the control after six months. However, BMI z-score and waist circumference measures did not reflect the benefits of this program. Trial registration Clinical trial number: NCT04155255, November 7, 2019 (Retrospective registered). National Medical Research Register: NMRR-13–439-16,563. Registered July 23, 2013. The intervention program was approved by the Medical Research and Ethics Committee (MREC), Ministry of Health Malaysia and the Educational Planning and Research Division (EPRD), Ministry of Education Malaysia. It was funded by the Ministry of Health Malaysia.